An exploration of the effects of social media on youth online and offline sociopolitical engagement. (March 2023) - Zyad, Hicham
On April 20th, 2018, Moroccan youths launched a boycott campaign on social media targeting three commercial brands. This incident has reinvigorated the debate on youth engagement in civic activism. Thus, this article compares Moroccan college-level students' civic engagement through formal processes and online social networking as well as predicting students' levels of engagement based on their demographic characteristics and political orientation variables. The analysis revealed that social media use was significantly correlated with youth virtual civic activities. Political interest and self-efficacy also had a significant impact on youth civic engagement. However, of the five demographic variables involved, only two were found to be significantly correlated with youth online civic activities. The study therefore identifies evidence corroborating other researchers' finding that Moroccan youth play a role in influencing policy and decision-making through informal channels of civic engagement.